PENGARUH GAYA KEPEMIMPINAN DELEGATIF DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CLIPAN FINANCE INDONESIA, TBK CABANG TANGERANG NEW-CAR ALAM SUTERA - Yanthi Meitry Gunawan; Ineke Al Hariri (Universitas Muhammadiyah Tangerang, 2019)
This study aims to determine the effect of Delegative Leadership Style and Work Discipline on employee performance at PT. Clipan Finance Indonesia, Tangerang New-Car Alam Sutera Branch. The approach and type of research with associative quantitative data, obtained a number of samples of 60 respondents from 60 populations using non probability sampling techniques, namely saturated samples. Statistical tests were carried out which included simple regression test, multiple regression test, simple correlation test, multiple correlation test, and determination of determination coefficient. And hypothesis testing is also done which includes partial test (t test) and simultaneous test (f test). The results showed that the influence of the Delegative Leadership Style and Work Discipline on employee performance, with a contribution of determination (R²) of 0.500 or 50%. And the remaining 50% is explained by other variables outside the concept and the resulting regression equation is Y = 6.704 + 0.419 X ₁ + 0.403 X ₂ . Based on the regression equation above, it can be explained that the constant value (bₒ) of 6.704 states that the value of the employee's performance level will still be 6.704 even though the independent variable is not there (0). Value (b ₁ ) of 0.419, this indicates a positive and significant influence of the variable delegative leadership style on employee performance of 0.419. This shows if delegative leadership style 1, then employee performance will increase by 0.419. Value (b ₂ ) of 0.403, this indicates a positive and significant effect of work discipline variables on employee performance 0.403. This shows that if the employee's performance is 1, it will increase by 0.403.Keywords: Delegative Leadership Style, Work Discipline, and Employee Performance